Overstory Longleaf Pines and Hardwoods Create Diverse Patterns of Energy Release and Fire Effects During Prescribed Fire - Whelan, Andrew W.; Bigelow, Seth W.; O’Brien, Joseph J. (Frontiers in Forests and Global Change, 2021)
Litter from pine trees in open woodlands is an important fuel for surface fires, but litter from hardwood species may quell fire behavior. Lower intensity fires favor hardwood over longleaf pine regeneration, and while overstory hardwoods are important sources of food and shelter for many wildlife species, too many could result in canopy closure and a loss of ground layer diversity. Although some researchers have found synergies in fire effects when leaves of different species are combined, field tests of effects of tree guild diversity on fire behavior are lacking from the literature. We used neighborhood modeling to understand how diverse overstory trees in longleaf pine forests affect fire radiative energy density (FRED), and to determine the effect on top-kill of shrub-form hardwood trees. We measured the effects of three guilds of overstory trees (longleaf pine, upland oaks, and mesic oaks) on FRED, and related FRED to post-fire damage in four guilds of understory hardwoods (sandhill oaks, upland oaks, mesic oaks, and fleshy-fruited hardwoods). We found that FRED increased 33-56% near overstory longleaf pine but decreased 23-37% near overstory mesic oaks. Additive models of FRED performed well and no synergies or antagonisms were present. Seventy percent of stems of understory hardwoods survived fire with energy release typical of dormant-season fires in canopy gaps and near overstory mesic oaks. We also found that among understory trees > 2m tall, upland and sandhill oaks were more likely than mesic oaks or fleshy-fruited hardwoods to avoid top-kill. We conclude that neighborhood models provide a method to predict longleaf pine forest structure and composition that allows for the ecological benefits of overstory hardwoods while maintaining ground-layer diversity. To maintain hardwood control, fire practitioners may need to select fire weather conditions to increase fire behavior especially during dormant-season burns.